Engaging Gypsy, Roma, and Traveller Communities in Research: Maximizing Opportunities and Overcoming Challenges. (July 2019) - Condon, Louise; Bedford, Helen; Ireland, Lana; Kerr, Susan; Mytton, Julie; Richardson, Zoe; Jackson, Cath
Gypsy, Roma, and Traveller people are marginalized worldwide and experience severe health inequalities, even in comparison to other ethnic minority groups. While diverse and hard to categorize, these communities are highly cohesive and members have a strong sense of identity as a group apart from the majority population. Researchers commonly experience challenges in accessing, recruiting, and retaining research participants from these communities, linked to their outsider status, insular nature, and history of discrimination. In this article, the challenges and the opportunities of engaging Gypsies, Roma, and Travellers in a multicenter qualitative research project are discussed. The management of public involvement and community engagement in this U.K.-based project provides insights into conducting research effectively with ethnically and linguistically diverse communities, often considered to be "hard to reach."